(untitled) (Journal of actual problems of jurisprudence, 2022)
The purpose of the article is to analyze the concept of substandard products (substandard goods) as an important element of the conceptual apparatus that provides legal regulation of trade and trade law. The article examines the concept of substandard products (substandard goods), which, according to the author, does not have proper legislative regulation and, in fact, has a complex structure. Based on the analysis of approaches that been developed in practice, the author proposes to understand substandard and poor-quality goods, the actual characteristics (properties) of which do not correspond to those declared in accordance with the requirements of regulatory legal acts or regulatory documentation. It is proposed to refer to the types of substandard products: 1) falsified products, i.е. products declared in accordance with the requirements of regulatory legal acts or regulatory documentation, composition of which has been consciously (deliberately) changed; 2) low-quality products - the composition of which was subjected to change due to negligence. As the main research method, we should designate the comparative legal method, as well as the method of situational synthesis, which allows us to distinguish between concepts based on real differences, the subtleties of which are not taken into account when developing and using concepts in real situations. The author substantiates the need to distinguish between the illegal circulation of substandard products (products with a changed composition) and the illegal circulation of conditioned products, the composition of which meets the requirements stated in accordance with regulatory legal acts and regulatory documents, but the circulation of such products is carried out in violation of exclusive rights, requirements for its registration and certification. Keywords: industrial products, substandard products, counterfeit products, substandard products, Eurasian Economic Union